Flexible and Ultrahigh Through‐Plane Thermally‐Conductive Polyethylene/Boron Nitride Nanocomposite Films. Issue 1 (17th November 2021) - Zhang, Ri‐Chao; Huang, Zirui; Zhong, Meiling; Ji, Dehui; Lu, Ai; Zhang, Quanchao; Lin, Yuanfei; Joseph, Paul; Zhang, Jiali; Sun, Dan
Abstract: Polymers with relatively higher thermal conductivity are in great demand for many advanced functional applications that often require thermally conductive as well as flexible materials. However, enhancing the thermal conductivity of polymers, while maintaining their mechanical properties, is still a formidable challenge. Here it is reported on the successful fabrication of polyethylene (PE)/boron nitride nanoplate (BNNP) nanocomposite films, with excellent flexibility and ultrahigh through‐plane thermal conductivity, by a uniaxially hot‐stretching process. Results from this study show that the nanocomposite films with ϕ v = 6.7 vol% BNNPs, under low stretching ratio ( Λ = 5), exhibit a through‐plane thermal conductivity of ≈14.54 W m −1 K −1, about 44.4 times higher than the corresponding bulk value for PE (0.32 W m −1 K −1 ), while also having improved the Young's modulus of elasticity. The theoretical analysis also shows that such a dramatic enhancement can be attributed to the formation of a 3D continuous network structure within the nanocomposite films. Thus, these flexible films offer possibilities as passive heat exchange matrices in various advanced applications that often require the materials with higher flexibility, lighter weight, easy/scalable processing attributes, and with a higher thermal conductivity. Abstract : A 3D continuous network structure within nanocomposite films is formed after a hot‐stretching process. In this continuous network structure, the aligned lamellae are bridged by boron nitride nanoplates (BNNPs). Through BNNPs, continuous transportation channels for phonons can be established, and therefore increase the phonon mean free paths, resulting in great enhancement of thermal conductivity.